Internationalization of higher education: case study — China, Turkey - Baikushikova, G.; Umbetova, N.; Augan, M.; Shukirbayeva, A. (KU Publ., 2021)
For the past two decades internationalization of higher education institutions has been increasing in terms of its scope, volume and complexity. It has also been referred to as a worthwhile ‘business’ which involves gains for students, universities and other stakeholders. The article considers approaches to the interpretation of the concept of “internationalization” by foreign authors, main forms and elements of internationalization of higher education institutions, and identifies the features of internationalization of higher education. Taking into account the impact of the globalization process on internationalization of universities, the article analyzes the current level of internationalization of higher education in the sectors of China and Turkey in a pragmatic manner. This article provides an empirical model based on data analysis, and also highlights significant aspects of internationalization of higher education. We hope that the article will consider these points and provide long term strategies to pursue a more standardized education system as a model for Central Asian states.
Жоғары білімнің интернационалдануы: Қытай, Түркия мысалында
Интернационализация высшего образования: на примере Китая, Турции
Keywords: internationalization; higher education; China; Turkey; universities; Central Asia; academic mobility; integration processes